David J. Conrads letter to Carl J. Bendorf regarding bird sightings, fall 1988 - Conrads, David J.et al (1988)
Field notes contributed by David J. Conrads in a letter to Carl J. Bendorf. The field notes include a detailed description of a Golden Eagle. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed